The Methodology Of Economic Behavior Research: Pluralism Of Approaches - Ирина Евгеньевна Финкельштейн (Journal of Economic Sociology, 2010)
The author tries to describe methodological basis for economic behavior relying on the economic theory and economic sociology assumptions. The author formulates the development tendencies for the methodology of economic behavior research. The paper discusses the following questions: the loss of leading positions in the structure of socio-economic knowledge by the economic imperialism; confirmation for the pluralism of approaches towards the description of economic behavior; setting up of social epistemology.